Muhammad Al-Fatih’s Leadership Strategy in the Conquest of Constantinople and the Prophetic Dream Foretold by the Prophet - Hakim, Eka Rizky; Maulidia, Nabila; Maulana, Ahmad Reynaldi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
<div class="[–thread-content-max-width:32rem] @[34rem]:[–thread-content-max-width:40rem] @[64rem]:[–thread-content-max-width:48rem] mx-auto flex max-w-(–thread-content-max-width) flex-1 text-base gap-4 md:gap-5 lg:gap-6 group/turn-messages focus-visible:outline-hidden" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="a1fe07fd-47d7-4d54-9701-edb1c09a83ef" data-message-model-slug="gpt-4o"> This study aims to examine Muhammad Al-Fatih’s leadership in the conquest of Constantinople, a city whose fall enabled centuries of Ottoman dominance in both Asia and Europe. It also seeks to understand the key factors behind his success, which stemmed from his praiseworthy character traits—commitment, bravery, intelligence, discipline, sincerity, knowledge, and strong determination—based on sources from Islamic historical literature. The research uses a library research methodology, with data drawn from various secondary sources including journals, historical articles, and theses. A descriptive analysis is employed to explore Muhammad Al-Fatih’s life journey from childhood to his rise as Sultan and his eventual conquest of Constantinople in accordance with the Prophet Muhammad’s teachings. A qualitative analysis is also used to interpret the religious, strategic, and leadership factors involved during his reign. The findings show that Muhammad Al-Fatih excelled not only in military strategy and leadership but also held firmly to a strong religious vision and mission, which enabled him to fulfill the prophetic dream (or prophecy) of the Prophet Muhammad (PBUH) regarding the conquest of Constantinople. In conclusion, his success was not merely the result of physical strength but was also supported by deep faith and exceptional strategic leadership abilities.